Synthesis, spectroscopic characterization and thermogravimetric analysis of two series of substituted (metallo)tetraphenylporphyrins - Al-Shewiki, Rasha K.; Mende, Carola; Buschbeck, Roy; Siles, Pablo F.; Schmidt, Oliver G.; Rüffer, Tobias; Lang, Heinrich (Beilstein Journal of Nanotechnology, 2017)
Subsequent treatment of H2TPP(CO2H)4 (tetra(p-carboxylic acid phenyl)porphyrin, 1) with an excess of oxalyl chloride and HNR2 afforded H2TPP(C(O)NR2)4 (R = Me, 2; iPr, 3) with yields exceeding 80%. The porphyrins 2 and 3 could be converted to the corresponding metalloporphyrins MTPP(C(O)NR2)4 (R = Me/iPr for M = Zn (2a, 3a); Cu (2b, 3b); Ni (2c, 3c); Co (2d, 3d)) by the addition of 3 equiv of anhydrous MCl2 (M = Zn, Cu, Ni, Co) to dimethylformamide solutions of 2 and 3 at elevated temperatures. Metalloporphyrins 2a–d and 3a–d were obtained in yields exceeding 60% and have been, as well as 2 and 3, characterized by elemental analysis, electrospray ionization mass spectrometry (ESIMS) and IR and UV–vis spectroscopy. Porphyrins 2, 2a–d and 3, 3a–d are not suitable for organic molecular beam deposition (OMBD), which is attributed to their comparatively low thermal stability as determined by thermogravimetric analysis (TG) of selected representatives.
Keywords: electrospray ionization mass spectrometry; IR spectroscopy; metalloporphyrin; porphyrin; thermogravimetry; UV–vis spectroscopy